Frequency scanned interferometry (FSI): The basis of a survey system for ATLAS using fast automated remote interferometry - FoxMurphy, A; Howell, D; Nickerson, R; Weidberg, A (1996)
A novel optical survey system for continuous alignment of HEP experiments is described. The complete survey system is outlined and the underlying measurement technique, FSI, is described in detail. Preliminary findings made with a laboratory demonstration system for FSI are presented.